A new oxidative reagent synthesis and its applications: Tetrakis-(2,4,6-trimethylpyridine)silver(I) dichromate (T-TMPSDC) - Aydin, Fatma; Dersin, Semih (European Journal of Chemistry, 2017)
Tetrakis-(2,4,6-trimethylpyridine)silver(I) dichromate (T-TMPSDC) was easily synthesized by addition of 2,4,6-trimethylpyridine to an aqueous precipitation of silver dichromate and characterized thoroughly, using spectroscopic and others analytical methods such as FT-IR, 1H NMR, 13C NMR, DTA, SEM-EDS and XRD. When T-TMPSDC was used as an oxidative reagent, it showed selectivity in the oxidation of primary, secondary and benzylic alcohols to their corresponding carbonyl compounds in presence of benzylic carbons and arenes such as tetraline, anthracene and phenanthrene.